The Correlation between Feeding Habit Factor and The Incidence of Stunting in Children Under Five Years - Elni Elni; Erna Julianti (Jurnal Keperawatan Padjadjaran, 2020)
Stunting becomes one of the prior nutritional problems in Bangka Belitung Islands Province, especially West Bangka Regency with a high stunting rate. Feeding habit in children will continuously influence nutrition fulfillment that will directly affect the incidence of stunting. This study aimed at identifying the correlation between feeding habit (beliefs, feeding practices, and children’s eating behavior and the incidence of stunting in children under five years in West Bangka Regency. This was a quantitative study with across-sectional approach. The total sample was 186 respondents taken using a consecutive sampling technique. The instruments for data collection were height measuring instrument, height-for-age graphic according to WHO 2006 to see the z-score and the under-five children’s characteristics questionnaire, a questionnaire of food beliefs, feeding practices questionnaire (CFQ), and child eating behaviour (CEBQ). The analysis in this study used a Chi-Square test. The result showed that there was a significant correlation between child eating behavior and the incidence of stunting in children under five in West Bangka Regency with a p-valueof 0.001 (p<0.05) and an OR of 4.89. It indicates that the low eating behavior in children under five has a possibility of 4.89 times higher to experience stunting than the high eating behavior. Also, there is no correlation between mothers’ beliefs and feeding practices with the incidence of stunting (p-value of 0.2 & 0.7 respectively). This study is expected to form a peer group for the community of under-five children’s families to prevent and improve the children’s nutritional status and development optimally.